BRAND DIFFERENTIATION STRATEGIES AND SUSTAINABLE COMPETITIVE ADVANTAGE OF MTN NIGERIA IN SOUTH-SOUTH REGION - Okpighe, Spencer G. O.; Moruku, Robert K. (African Journal of Social and Behavioural Sciences, 2025)
This study examines brand differentiation strategies and sustainable competitive advantage of MTN Nigeria in the South-South region. The specific objectives are to investigate the effect of brand trust, brand image, brand awareness, and service quality on MTN Nigeria’s sustainable competitive advantage. This study adopted a cross-sectional method for data collection and empirical analysis. A stratified random sampling technique was used. A sample size of 357 was selected out of 5000 staff of MTN Retail Network Centres. The sample size was calculated using Krejcie and Morgan’s table and Bowley’s allocation formula. The study adopted a 5-point Likert scale structured questionnaire. A test-retest reliability technique was used to determine the reliability of the instrument. Cronbach’s Alpha coefficient of 0.7 was generated. The data collected was analysed using correlation and regression analysis via the IBM Statistical Package for Social Sciences (SPSS), version 25. Findings showed that brand trust (ß = 0.258, p < 0.05), brand image (ß = 0.111, p < 0.05), brand awareness (ß = 0.567, p < 0.01), and service quality (ß = 0.465, p < 0.05) had a strong, significant, positive relationship with MTN Nigeria’s sustainable competitive advantage. The study revealed that brand differentiation strategies were responsible for 78% of the changes in the sustainable competitive advantage of MTN Nigeria. The study recommends, among others, that telecommunication companies should offer a distinguishable brand that has a quality that customers can trust, create a distinctive brand image in the public domain to enable customers’ brand acceptability, and increase market share through competitive performance.